Optimizing Frequency and Pulse Shape for Ultrasound Current Source Density Imaginag - Qin, Yexian (2012)
Electric field mapping is commonly used to identify irregular conduction pathways in the heart (e.g., arrhythmia) and brain (e.g., epilepsy). Ultrasound current source density imaging (UCSDI), based on the acoustoelectric (AE) effect, is a promising new technique for mapping electrical current in four dimensions with enhanced resolution. The frequency and pulse shape of the ultrasound beam affect the sensitivity and spatial resolution of UCSDI. In this study, we explore the effects of ultrasound transducer frequency bandwidth and coded excitation pulses for UCSDI and the inherent tradeoff between sensitivity and spatial resolution. We used both simulations and bench-top experiments to image a time-varying electrical dipole in 0.9% NaCl solution. To study the effects of ultrasound bandwidth, we chose two ultrasound transducers with different center frequencies (1.0 and 2.25 MHz). For coded excitation, we measured the AE voltage signal with different chirp excitations. As expected, higher bandwidth correlated with improved spatial resolution at the cost of sensitivity. On the other hand, chirp excitation significantly improved sensitivity (3.5 μV/mA) compared with conventional square pulse excitation (1.6 μV/mA) at 1 MHz. Pulse compression achieved spatial resolution similar to that obtained using square pulse excitation, demonstrating enhanced detection sensitivity without loss of resolution. Optimization of the time duration of the chirp pulse and frequency sweep rate can be further used to improve the quality of UCSDI.